A study on e-CRM applications for Indian fast food chains. (21st April 2011) - Rakesh, Sapna; Khare, Arpita
The changes in the lifestyle of Indian consumers have led to a rapid growth in fast food retail establishments in the country in the past few years. With the fast changing demographics and economic environment of the country, customer relationship management (CRM) and e-CRM (electronic CRM) are poised to grow with many business moving online not due to choice, but due to necessity (Feinberg et al., 2002). Managing relationships with customer becomes an important responsibility of the fast food outlets, with considerable attention being given to relationship marketing, CRM and e-CRM. Marketing strategies cannot ignore the electronic component for maintaining relationship with customers. It is believed that e-CRM can be an important tool in fostering relationships with customers and enabling companies in developing profitable relationships. This paper explores issues related to the e-CRM tools employed by the fast food establishments to maintain customer relationship and the extent to which they are successful. There is scant research related to the topic in India so far. This is an initial endeavour by the researchers to provide insights to fast food vendors, academicians and the policy makers on improving the reach of the CRM applications for maintaining profitable relationships with their valued customers.